Clinical Image Quality and Sensitivity in an Organized Mammography Screening Program. Issue 1 (February 2018) - Théberge, Isabelle; Guertin, Marie-Hélène; Vandal, Nathalie; Daigle, Jean-Marc; Dufresne, Michel-Pierre; Wadden, Nancy; Shumak, Rene; Samson, Caroline; Langlois, André; Larocque, Isabelle; Perron, Linda; Pelletier, Éric; et al.
Purpose: The study sought to examine the association between clinical image quality of mammograms and screening sensitivity. Methods: Four radiologists evaluated the clinical image quality of 374 invasive screen-detected cancers and 356 invasive interval breast cancers for which quality evaluation of screening mammograms could be assessed from cancers diagnosed among participants in the Quebec Breast Cancer Screening Program in 2007. Quality evaluation was based on the Canadian Association of Radiologists accreditation criteria, which are similar to those of the American College of Radiology. The association between clinical quality and screening sensitivity was assessed by logistic regression. Adjusted sensitivity and adjusted sensitivity ratios were obtained through marginal standardization. No institutional review board approval was required. Results: A proportion of 28% (206 of 730) of screening mammograms had lower overall quality for the majority of assessments. Positioning was the quality attribute that was the most frequently deficient. The 2-year screening sensitivity reached 68%. Sensitivity of screening was not statistically associated with the overall quality (ratio of 2-year sensitivity = 1.03; 95% confidence interval: 0.93-1.15) or with any quality attributes (positioning, exposure, compression, sharpness, artifacts, contrast). Results were similar for the 1-year sensitivity. Conclusions: Although not all mammograms in the Quebec screening program met the optimum quality required by the Canadian Association of Radiologists or American College of Radiology accreditation, the screening mammograms produced in this population-based organized screening program reached a high enough level of quality so that the remaining variation in quality is too little to impair screening sensitivity.